A Model for Good Governance of Healthcare Technology Management in the Public Sector: Learning from Evidence-Informed Policy Development and Implementation in Benin - Houngbo, P.Th.; Coleman, H. L. S.; Zweekhorst, M.; De Cock Buning, Tj; Medenou, D.; Bunders, J. F. G. (My University, 2017)
Good governance (GG) is an important concept that has evolved as a set of normative principles for low- and middle-income countries (LMICs) to strengthen the functional capacity of their public bodies, and as a conditional prerequisite to receive donor funding. Although much is written on good governance, very little is known on how to implement it. This paper documents the process of developing a strategy to implement a GG model for Health Technology Management (HTM) in the public health sector, based on lessons learned from twenty years of experience in policy development and implementation in Benin. The model comprises six phases: (i) preparatory analysis, assessing the effects of previous policies and characterizing the HTM system; (ii) stakeholder identification and problem analysis, making explicit the perceptions of problems by a diverse range of actors, and assessing their ability to solve these problems; (iii) shared analysis and visioning, delineating the root causes of problems and hypothesizing solutions; (iv) development of policy instruments for pilot testing, based on quick-win solutions to understand the system’s responses to change; (v) policy development and validation, translating the consensus solutions identified by stakeholders into a policy; and (vi) policy implementation and evaluation, implementing the policy through a cycle of planning, action, observation and reflection. The policy development process can be characterized as bottom-up, with a central focus on the participation of diverse stakeholders groups. Interactive and analytical tools of action research were used to integrate knowledge amongst actor groups, identify consensus solutions and develop the policy in a way that satisfies criteria of GG. This model could be useful for other LMICs where resources are constrained and the majority of healthcare technologies are imported
Keywords: Good governance; healthcare technologies